2017
DOI: 10.1038/s41598-017-13711-7
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 recognizes the N-terminus of huntingtin involved in regulation of huntingtin aggregation by USP19

Abstract: Huntington’s disease (HD) is caused by aberrant expansion of polyglutamine (polyQ) in the N-terminus of huntingtin (Htt). Our previous study has demonstrated that HSP90 is involved in the triage decision of Htt, but how HSP90 recognizes and regulates Htt remains elusive. We investigated the interaction between HSP90 and the N-terminal fragments of Htt (Htt-N), such as the N-terminal 90-residue fragment (Htt-N90). Our results showed that HSP90 binds to the N-terminal extreme of Htt-N in a sequence just ahead of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 67 publications
(78 reference statements)
1
38
0
Order By: Relevance
“…of HSP90, and direct binding of HSP90 to exon 1 at N17 was recently demonstrated [51] . This study also showed that USP19 may be subsequently recruited to HSP90-HTT fragment complexes and can then deubiquitylate HTT, leading to accumulation of insoluble HTT aggregates containing HSP90.…”
Section: Hd Modulates Function Of the Chaperone And Autophagy Machinerymentioning
confidence: 97%
See 1 more Smart Citation
“…of HSP90, and direct binding of HSP90 to exon 1 at N17 was recently demonstrated [51] . This study also showed that USP19 may be subsequently recruited to HSP90-HTT fragment complexes and can then deubiquitylate HTT, leading to accumulation of insoluble HTT aggregates containing HSP90.…”
Section: Hd Modulates Function Of the Chaperone And Autophagy Machinerymentioning
confidence: 97%
“…Surprisingly, few DUBs have been reported to deubiquitylate HTT. ATXN3, a DUB that itself contains a polyQ tract, and USP19 are the only known DUBs to target HTT [49][50][51] besides UPS. Monoubiquitylation or ubiquitin conjugation of proteins by different linkages of chains are recognised by a range of proteins containing ubiquitin binding domains (UBDs) or ubiquitininteracting motifs (UIMs) and are essential in numerous cell signalling pathways.…”
Section: Cellular Proteostasis Is Disrupted In a Number Of Neurodegenmentioning
confidence: 99%
“…At the C-terminal end, USP19 harbors a transmembrane domain mapping its function initially to endoplasmic-reticulum-associated degradation and cellular homeostasis by supporting protein quality control and clearing misfolded proteins, mainly in interaction with the chaperone Hsp90 2528 . USP19 seems to contribute different biological mechanisms such as protection against muscle wasting 2931 , formation of protein aggregation 28,32 or cell proliferation 33,34 . There, USP19 depletion inhibited proliferation of prostate cancer and breast epithelial cell lines suggesting it to have oncogenic properties 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the proteins upregulated suggested a role in stabilizing, rather than degrading Httex1. This included deubiquitinating enzyme Usp19, which has been previously reported to stabilize mutant Httex1 levels and promote its aggregation into less toxic aggregates by Hsp90 (102,103). Rock2 was also increased, which has previously been suggested to slow degradation of Httex1 (104).…”
Section: Supplementary Note 1 Expanded Discussion Of Proteins That Cmentioning
confidence: 96%